The burden of entheseal involvement in systemic lupus erythematosus: a comparative ultrasonograghic study - Emerah, Ahmed; Mostafa, Shaimaa; Kotb, Lobna; Amer, Yomna; Ismail, Basma; Sarhan, Shymaa A. (Clinical rheumatology, 2024)
Background Imaging is crucial for identifying and diagnosis of the musculoskeletal (MSK) symptoms, which are one of the most typical manifestations of systemic lupus erythematosus (SLE). For the joints, tendons, and entheseal sites, ultrasonography has shown to be sensitive and accurate for the diagnosis of both inflammation and structural damage. Aim The goal of the current investigation is to determine the prevalence and the distribution of entheseal abnormalities in SLE patients, using musculoskeletal ultrasonography (MSUS) and to assess the relationship between entheseal sonographic changes and the SLE disease activity. Patients and methods One hundred sixty-eight subjects were studied (56 SLE patients, 56 psoriatic arthritis (PSA) patients, and 56 normal cases). To compare the frequency and the distribution of entheseal involvement, high-resolution MSUS was conducted to assess the entheseal sites of all patients in accordance with the Madrid Sonographic Enthesitis Index (MASEI). Results Clinical enthesitis was detected in 39.3% of the SLE patients using the Leeds Enthesitis Index compared to 71% detected via US examination, indicating a high proportion of subclinical enthesitis in our SLE patients. The most frequently affected enthesis was the distal insertion of the patellar tendon at the tibial tuberosity which was detected in 41% of SLE patients. Enthesitis was significantly more frequent in PSA patients (100%) compared to SLE patients (71.4%) ( p < 0.05) and more significantly frequent in SLE patients compared to the healthy controls (19.6%). There was a significant correlation between MASI and SLEDAI scores ( r = 0.250*, p = 0.048) and the total protein in 24 h ( r = 0.289*, p = 0.031). In addition, there was an inverse significant correlation between MASEI and serum albumin ( r =  − 0.324*, p = 0.015). Conclusion In SLE patients, enthesitis is frequently clinical and ultrasound-verified. The most impacted enthesis is at the insertion of the quadriceps tendon. Enthesitis presence and the rise in the MASI score can serve as indicators of the severity of the SLE disease. Key Points • The most impacted entheseal site lies at the insertion of the quadriceps tendon. • The presence and the rise in MASEI score can serve as indicators of the severity of the SLE disease.